The Relationship Between Pastry and Bakery Training Strategies and Participants' Entrepreneurial Interests At The LKP IBTI Learning Center Bukittinggi - Kishenta, Brenda Dwitama; Wisroni, Wisroni (Universitas Negeri Padang, 2023)
This research was motivated by the low interest in entrepreneurship in pastry and bakery training participants. This research aims to look at pastry and bakery training strategies, the entrepreneurial interest of pastry and bakery training participants, and to see the relationship between training strategies and the entrepreneurial interest of pastry and bakery training participants at the LKP IBTI Learning Center Bukittinggi. This research uses a quantitative approach with a correlational type of research. The population in this study was 31 trainees who took part in pastry and bakery training at the LKP IBTI Learning Center Bukittinggi. Meanwhile, 80% of the population was taken as a sample, namely 25 people using cluster random sampling techniques. The data collection technique uses a questionnaire. Data analysis techniques use percentage formulas and rank order correlation formulas. The results of this research show that (1) pastry and bakery training strategies are still less effective, (2) interest in entrepreneurship in pastry and bakery training participants is still low, (3) there is a relationship between training strategies and interest in entrepreneurship, the relationship is declared significant because it is categorized as very high. It is recommended that instructors pay attention to the diversity of training participants so that participants feel appreciated and are serious about carrying out the training, so that training results are obtained as expected. It is recommended for LKP managers to increase the development of the PKW program implemented by LKP in the future in an effort to make graduates more interested in entrepreneurship. Future researchers will be able to identify other characteristics or variables that have not been studied in this research for further research.Keywords: Training Strategy, Interest in Entrepreneurship